Anterior Column Reconstruction vs Pedicle Subtraction Osteotomy for Severe Sagittal Plane Deformity: Early Clinical and Radiographic Outcomes Using a Hyperlordotic Expandable Lateral Interbody Device. (1st September 2019) - Massie, Lara Walsh; Macki, Mohamed; Zakaria, Hesham M; Gilmore, Michelle; Basheer, Azam; Chang, Victor W; La Marca, Frank
Abstract: INTRODUCTION: Anterior Column Reconstruction (ACR) is an increasingly utilized minimally invasive alternative to Pedicle Subtraction Osteotomy (PSO) for correction of sagittal plane deformity in patients with an available unfused lumbar disc. METHODS: Fifteen consecutive patients with significant sagittal plane imbalance (SVA > 10 cm or PI-LL mismatch/planned correction > 30?) after prior lumbar fusion were analyzed. Patients underwent either an ACR (N = 11) using an expandable, hyperlordotic lateral interbody device if possible via an unfused disc space, or PSO (n = 4). RESULTS: There were no significant differences between the baseline sagittal parameters in the ACR and PSO groups: PI: 59.09? vs 57.67?, P = .88; LL 18.36? vs 28.50?, P = .38; PT: 32.72? vs 37.00?, P = .64; SVA: 12.72 cm vs 11.95 cm P = .77; segmental angulation 2.72? vs 2.75?, P = .99. ACR produced significant improvements in sagittal parameters after surgery compared with preoperative parameters: LL 55.27?, P = .0001; Pi-LL Mismatch 3.45?, P = .0001; PT 22.45?, P = .0254; SVA 4.621 cm P = .0019; segmental angle 25.09?, P < .0001. PSO also produced significant segmental lordosis (29.00?, P = .0032), which was not significantly different from the correction achieved by ACR (25.09? vs 29.00?, P = .47). In ACR, an average of 24.31? of lordosis was achieved at the index level, with an average cage expansion of 24.08?. There was no significant difference in the number of levels fused posteriorly between the ACR and PSO groups (7 vs 8.75 levels, P = .175) or length of surgery (375.25 min vs 370.5 min, P = .47). However, there was significantly less blood loss in the ACR group (311.15 mL vs 962.5 mL, P = .0004) and shorter length of stay (7.41 d vs 11 d, P = .034). CONCLUSION: ACR with a hyperlordotic, expandable lateral interbody cage for significant sagittal deformity produced an equivalent degree of sagittal correction to PSO with significantly less blood loss and shorter hospital length of stay.